Stability Estimates for an Inverse Problem for the Linear Boltzmann Equation - Cipolatti, Rolci; Motta, Carlos M.; Roberty, Nilson C. (Revista Matemática Complutense, 2006)
In this paper we consider the inverse problem of recovering the total extinction coefficient and the collision kernel for the time-dependent Boltzmann equation via boundary measurements. We obtain stability estimates for the extinction coefficient in terms of the albedo operator and also an identification result for the collision kernel.